#### Answer

$68=r$

#### Work Step by Step

Dividing both sides by $
-1
$, then the solution to the given equation, $
-68=-r
$, is
\begin{array}{l}
\dfrac{-68}{-1}=\dfrac{-r}{-1}
\\\\
68=r
.\end{array}

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$68=r$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.